Magnetron sputtering of high temperature composite ceramics AlN-TiB₂-TiSi₂ - Torianik, I.N.; Beresnev, V.M.; Pogrebnjak, A.D.; Sobol, O.V.; Beresneva, Ye.V.; Podcherniaieva, I.A.; Kropotov, A.Yu.; Stiervoiedov, N.G.; Turbin, P.V.; Kolesnikov, D.A.; Grankin, S.S.; Nyemchenko, U.S.; et al. (Физическая инженерия поверхности, 2013)
By means of the magnetron sputtering method using the DC and pulsed voltages applied to the target,
the coatings based on AlN-TiB₂-TiSi₂ ceramics were obtained. An amorphous-like structure of the
obtained coatings was revealed. It had the area of ordering ~ 1 nm and the viscoplasticity coefficient
of 0.07. The hardness of the coatings reaches 15.3 GPa, and the modulus of elasticity is 206 GPa.
The coatings are characterized by high adhesion strength to the substrate. Магнетронным методом распыления, с применением постоянного и импульсного напряжений
намишень, полученыпокрытия на основе керамики AlN-TiB₂-TiSi₂. Выявлено аморфноподобную
структуру сформированных покрытий с областью упорядочения ~ 1 нм и коэффициентом вязкопластичности 0,07. Твердость покрытий достигает 15,3 ГПа, а модуль упругости составляет 206 ГПа. Покрытия характеризуются высокой адгезионной прочностью по отношению к подложке. Магнетронним методом розпилення, іззастосуванням постійної та імпульсної напруг на мішень,
отримані покриття на основі кераміки AlN-TiB₂-TiSi₂. Виявлено аморфноподібну структуру
сформованих покриттів із областю впорядкування ~1 нм і коефіцієнтом в’язкопластичності
0,07. Твердість покриттів досягає 15,3 ГПа, а модуль пружності складає 206 ГПа. Покриття
характеризуються високою адгезійною міцністю по відношенню до підкладинки.